Absenteeism: Key Driver of Poor Performance in Primary Education - UNICEF (UNICEF, 2016)
With the introduction of Universal Primary Education (UPE) in 1997, Government committed to provide free education to all children of primary school going age. Through the UN Millennium Development Goals (MDGs), Uganda further committed to ensure delivery of a full course of primary education to all children by 2015. According to the MDG 2015 report, notable gains attributed to UPE include increased enrollment, a general upsurge in primary school completion, and the elimination of gender disparities between girls’ and boys’ completion rates. Achievements notwithstanding, the efficiency of Uganda’s primary education is low - survival rate to P7 stands at 32.1%, repetition at 10.2% (EMIS, 2014), and teacher absenteeism is estimated at 20-30% (NPA, 2015).